Affinity-controlled protein encapsulation into sub-30 nm telodendrimer nanocarriers by multivalent and synergistic interactions. (September 2016) - Wang, Xu; Shi, Changying; Zhang, Li; Bodman, Alexa; Guo, Dandan; Wang, Lili; Hall, Walter A.; Wilkens, Stephan; Luo, Juntao
Abstract: Novel nanocarriers are highly demanded for the delivery of heterogeneous protein therapeutics for disease treatments. Conventional nanoparticles for protein delivery are mostly based on the diffusion-limiting mechanisms, e.g., physical trapping and entanglement. We develop herein a novel linear-dendritic copolymer (named telodendrimer) nanocarrier for efficient protein delivery by affinitive coating. This affinity-controlled encapsulation strategy provides nanoformulations with a small particle size (<30 nm), superior loading capacity (>50% w/w) and maintained protein bioactivity. We integrate multivalent electrostatic and hydrophobic functionalities synergistically into the well-defined telodendrimer scaffold to fine-tune protein binding affinity and delivery properties. The ion strength and density of the charged groups as well as the structure of the hydrophobic segments are important and their combinations in telodendrimers are crucial for efficient protein encapsulation. We have conducted a series of studies to understand the mechanism and kinetic process of the protein loading and release, utilizing electrophoresis, isothermal titration calorimetry, Förster resonance energy transfer spectroscopy, bio-layer interferometry and computational methods. The optimized nanocarriers are able to deliver cell-impermeable therapeutic protein intracellularly to kill cancer cells efficiently. In vivo imaging studies revealed cargo proteins preferentially accumulate in subcutaneous tumors and retention of peptide therapeutics is improved in an orthotopic brain tumor, these properties are evidence of the improved pharmacokinetics and biodistributions of protein therapeutics delivered by telodendrimer nanoparticles. This study presents a bottom-up strategy to rationally design and fabricate versatile nanocarriers for encapsulation and delivery of proteins for numerous applications. Graphical abstract: